Evolutionary conservation of the placodal transcriptional network during sexual and asexual development in chordates - Gasparini, F; Degasperi, V; Shimeld, S; Burighel, P; Manni, L (2013)
Background: An important question behind vertebrate evolution is whether the cranial placodes originated de novo, or if their precursors were present in the ancestor of chordates. In this respect, tunicates are of particular interest as they are considered the closest relatives to vertebrates. They are also the only chordate group possessing species that reproduce both sexually and asexually, allowing both types of development to be studied to address whether embryonic pathways have been co-opted during budding to build the same structures. Results: We studied the expression of members of the transcriptional network associated with vertebrate placodal formation (Six, Eya, and FoxI) in the colonial tunicate Botryllus schlosseri. During both sexual and asexual development, each transcript is expressed in branchial fissures and in two discrete regions proposed to be homologues to groups of vertebrate placodes. Discussion: Results reinforce the idea that placode origin predates the origin of vertebrates and that the molecular network involving these genes was co-opted in the evolution of asexual reproduction. Considering that gill slit formation in deuterostomes is based on similar expression patterns, we discuss possible alternative evolutionary scenarios depicting gene co-option as critical step in placode and pharynx evolution. Developmental Dynamics 242:752-766, 2013. © 2013 Wiley Periodicals, Inc.